Evaluation of selective media for bifidobacteria in poultry and rabbit caecal samples - Rada, V; Sirotek, K; Petr, J (Zentralblatt fur Veterinarmedizin. Reihe B. Journal of veterinary medicine. Series B, 1999)
Five media were evaluated to determine their selectivity for Bifidobacterium sp. in hen and rabbit caecal samples. The colonies arising on the plates inoculated with the caecal samples were Gram stained and screened for the presence of fructose-6-phosphate phosphoketolase activity. Rogosa agar modified by the addition of cysteine-hydrochloride (0.05% w/v), Beeren's agar (with 5 ml/l of propionic acid as a selective agent), BS 2 agar (containing per one litre sodium propionate 15 g, lithium chloride 3 g, paromomycin sulphate 50 mg, neomycin sulphate 200 mg), and Wilkins-Chalgren agar (MW) modified by the addition of acetic acid (1 ml/l) and mupirocin (100 mg/l) were selective for Bifidobacterium sp. from rabbit caecal samples. In contrast, only MW medium was suitable for the isolation and enumeration of bifidobacteria in hen caecal samples. In conclusion, the results suggest that MW agar showed the greatest selectivity. A further advantage of this medium is its case of preparation. Therefore this agar could contribute to the study of the effects of the ingestion both probiotics and prebiotics. Finally, it could be noted that the bifidobacteria selective media should be chosen in respect of the animal species origin of the sample tested.
Keywords: Chickens; Phenazines; Female; Aldehyde-Lyases; Gentian Violet; fenaziny; aldehydlyasy; Cecum; cékum; zvířata; Colony Count, Microbial; Culture Media; genciánová violeť; kultivační média; kur domácí; ženské pohlaví; počet mikrobiálních kolonií; králíci; Animals; Bifidobacterium; Rabbits